Pain Among Latvian Workers: General Prevalence vs. Registered Occupational Diseases - Kaluznaja, Darja; Reste, Jelena; Vanadzins, Ivars; Lakisa, Svetlana; Eglite, Maija (Frontiers in Public Health, 2022)
The problem of painful and disabling work-related musculoskeletal disorders (MSDs) is increasing in many employment sectors of Latvia. Official statistics may underestimate the proportion of affected employees, causing delays in preventive interventions, ineffective rehabilitation, and a reduction of the workforce. This study investigated the prevalence of painful health conditions among Latvian workers by analyzing survey data and comparing these to official statistics on registered occupational diseases (ODs). A total of 2,446 workers participated in the state-level “Work conditions and risks in Latvia, 2017–2018” survey that included questions about pain lasting longer than 3 days during the previous year. The frequency of subjective reports on the presence, severity, and location of pain and related behaviors was assessed in relation to sex, age, education, and job position. Descriptive statistics and crosstabulation with the chi-squared test as well as multinomial logistic regression were applied to the data. Overall, 27.7% of respondents (n=678) reported experiencing pain, predominantly in the lower back (14.3%) and mostly moderate (47.1%) or severe (45.1%). Only one-fifth of respondents (20.5%) took sick leave from work and one-third (29.0%) did not take action to alleviate their pain. Participants aged 55–74 years had a significantly higher odds ratio (OR) for pain in at least one body region—including hands and legs—than those aged 18–24 years. Women had significantly higher odds of headache (OR=2.55) and neck pain (OR=1.85) than men. Respondents with a primary or elementary education level had higher odds of pain in at least one body region (OR=1.60) and in the lower back (OR=1.86), while those with secondary education had higher odds of pain in hands (OR=1.51) than employees with higher education. Unskilled workers had significantly higher odds of pain in hands (OR=2.42) and legs (OR=2.12) than directors. Official data revealed a dramatic increase in the proportion of MSDs and related disabilities in the last decade, reaching 75.5% of all first registered ODs in 2019. These results demonstrate a high prevalence of painful conditions among Latvian employees; urgent attention to diagnostics, treatment, and prevention is needed to ensure the musculoskeletal health and productivity of this population.